2023
DOI: 10.1007/s11357-023-00811-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological markers of successful learning in healthy aging

Abstract: The capacity to learn and memorize is a key determinant for the quality of life but is known to decline to varying degrees with age. However, neural correlates of memory formation and the critical features that determine the extent to which aging affects learning are still not well understood. By employing a visual sequence learning task, we were able to track the behavioral and neurophysiological markers of gradual learning over several repetitions, which is not possible in traditional approaches that utilize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Van der Linden, Brédart, and Beerten (1994) suggest that attentional resources linked to the frontal cortex undergo a marked decline with aging whereas the storage capacity remains relatively unaffected 65 . Previously, we demonstrated that the slower and more variable timing of the stimulus identification process, reflected in the event-related potential P300 latency, suggests that despite the older participants engaging the memory formation process to a comparable extent as young participants, there is less time for it to translate the stimulus location information into a solidified memory trace 37 . This aligns with the cognitive slowing theory, suggesting that slower processing in older participants leads to reduced working memory capacity.…”
Section: Memory Performance Decline Associated With Agingmentioning
confidence: 89%
See 3 more Smart Citations
“…Van der Linden, Brédart, and Beerten (1994) suggest that attentional resources linked to the frontal cortex undergo a marked decline with aging whereas the storage capacity remains relatively unaffected 65 . Previously, we demonstrated that the slower and more variable timing of the stimulus identification process, reflected in the event-related potential P300 latency, suggests that despite the older participants engaging the memory formation process to a comparable extent as young participants, there is less time for it to translate the stimulus location information into a solidified memory trace 37 . This aligns with the cognitive slowing theory, suggesting that slower processing in older participants leads to reduced working memory capacity.…”
Section: Memory Performance Decline Associated With Agingmentioning
confidence: 89%
“…The data used in this study was recorded in our laboratory in the context of a larger project that aims to quantify age effects on eye movement behavior and electroencephalography (EEG) recordings of resting-state and other task-based paradigms 37,38 . The data was collected in two experimental sessions separated by a week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations